Melanoma maligna orbita: sebuah laporan kasus - Ni Luh Putu Nurindah Sukmawati; Putu Yuliawati; Ni Made Laksmi Utari (DiscoverSys Inc., 2022)
Introduction: Orbital melanoma (OM) is the most common type of primary intraocular neoplasm in adults. Although the incidence of OM is only 5% of melanoma tumors, OM causes death in 13% of melanoma tumors. The management of orbital melanoma originating from the uveal tissue is still controversial between surgical and nonsurgical therapy. Case Report: A male patient, 63 years old, complained that the patient's right eye was said to have appeared a lump since five months ago with a size of 6 x 6 x 7 cm, blackish red in color with clinical signs of malignancy. The patient underwent orbital exenteration and the patient's condition had no recurrence or other complaints until four months after the procedure. Conclusion: Orbital melanoma of uveal origin is a complex malignancy that requires a multidisciplinary approach to therapy and management. Early detection and adequate therapy are very important in increasing survival rates. Pendahuluan: Melanoma orbita (MO) merupakan tipe yang paling sering dari neoplasma primer intraokular pada dewasa. Meskipun insiden MO hanya 5% dari tumor melanoma, namun MO menimbulkan kematian pada 13% akibat tumor melanoma. Tatalaksana melanoma orbita yang berasal dari jaringan uvea sampai saat ini masih kontroversial antara terapi bedah dan nonbedah. Laporan Kasus: Seorang pasien laki-laki, 63 tahun, mengeluh mata kanan pasien dikatakan muncul benjolan sejak lima bulan yang lalu dengan ukuran 6 x 6 x 7 cm, berwarna merah kehitaman dengan klinis mengarah keganasan. Pasien dilakukan eksenterasi orbita dan kondisi pasien tidak terdapat kekambuhan ataupun keluhan lain hingga empat bulan setelah tindakan. Simpulan: Melanoma orbita yang berasal dari uvea merupakan keganasan yang kompleks yang membutuhkan pendekatan multidisiplin dalam terapi dan tatalaksana. Deteksi dini dan terapi yang adekuat sangat penting dalam upaya meningkatkan angka ketahanan hidup.